1980
DOI: 10.1159/000145167
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrical analysis of the aging process in human arteries and aorta

Abstract: Ultrastructural and morphometrical studies were conducted on vascular tissue from 205 human Japanese specimens ranging in age from 15 weeks’ gestation to 90 years. Comparison of aorta size with overall body length by allometry revealed that the aging aorta has growth and involution stages comparable to other organs, and that progressive increase in aortic diameter was the major involutional change. The cellular and extracellular components of the medial sections of thoracic and abdominal aorta, renal artery, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 2 publications
(2 reference statements)
4
40
0
Order By: Relevance
“…It has also been reported that the remodelling of the human thoracic aorta that occurs with ageing was associated with fragmentation of elastin fibres [94]. This fragmentation has also been reported in old, highly calcified thoracic aortas accompanied by atherosclerotic lesions [95].…”
Section: Effects Of Agementioning
confidence: 80%
See 1 more Smart Citation
“…It has also been reported that the remodelling of the human thoracic aorta that occurs with ageing was associated with fragmentation of elastin fibres [94]. This fragmentation has also been reported in old, highly calcified thoracic aortas accompanied by atherosclerotic lesions [95].…”
Section: Effects Of Agementioning
confidence: 80%
“…It was suggested that the decreased expression of fibulin-5 might impair the assembly of mature elastin in the ATA tissue, which could render the wall susceptible to dissection. This trend of decreased number of SMCs in the aortic wall is also common in ageing, hypertension and in presence of atheromatous plaque [88][89][90]94]. Disrupted and irregular elastin lamellae have been observed in the medial layer of dissecting ATAs with and without accompanying aneurysm, with some areas either being devoid of an elastin fibre framework, or having localized elastin fragmentation [56,59].…”
Section: Effects Of Diseasementioning
confidence: 94%
“…30 Furthermore, the aging process is characterized by a decrease in elastin and an increase in collagen fibers. 31,32 The more distensible elastin component is principally load bearing at lower pressures and small distensions, whereas at higher pressures, elastin together with stiffer collagen components are load bearing. 31,33 Thus, a dilated CCA in the elderly, with presumably reduced elastin lamellae and increased collagen components, seems to be stiffer.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the greater sensitivity of small artery changes is that the large arteries tend to increase in caliber with aging. 34 The effect of a reduction in arterial wall elastic properties on arterial distensibility might then be counterbalanced by a caliber increase in the large arteries but not in the small arteries. This caliber increase could maintain compliance despite a reduction of distensibility caused by structural or functional alterations in the wall.…”
Section: Figurementioning
confidence: 99%